Theory and Practice of Burning Solid Biofuels in Low-Power Heating Devices - Małgorzata Dula; Artur Kraszkiewicz (Energies)
Combustion is the most advanced and proven method on the market for using agricultural by-product residues and waste from the agri-food industry. Currently, a wide range of combustion technologies is used to produce heat and electricity in low-power heating devices (>50 kW) using various types of biofuels from biomass (woody biomass, herbaceous biomass, waste and residues from the agri-food industry). Combustion of biomass fuels, especially those of wood origin, causes lower carbon dioxide (CO2) and sulfur oxides (SOx) emissions into the atmosphere compared to coal combustion. The growing interest in solid biofuels has contributed to intensive activities on improving the combustion process and energy devices enabling effective and economic conversion of chemical energy contained in biomass into other usable forms such as heat, electricity. Having good quality fuel, it is necessary to ensure an appropriate, clean combustion technique, which allows to achieve the highest thermal efficiency of the heating device and at the same time the lowest emission of pollutants. The article presents issues related to the theory, characteristics of the combustion process and problems related to the formation of harmful chemical compounds nitrogen oxides (NOx), SOx, carbon monoxide (CO), particulate matter (PM) emitted to the atmosphere during the combustion process in low-power heating devices. The analysis indicates the possibility of minimizing undesirable phenomena during the combustion of these biofuels related to ash sintering, the formation of deposits, corrosion and improving the amount of condensable solid particles formed and therefore reducing the emission of gaseous products to the environment.